2015
DOI: 10.3109/02770903.2015.1080267
|View full text |Cite
|
Sign up to set email alerts
|

Association betweenCD14gene promoter polymorphisms with serum total-IgE and eosinophil levels in atopic and non-atopic asthma patients in a Chinese Han population

Abstract: There was a statistical association between the serum total-IgE level and the CD14 gene promoter SNPs in the non-atopic asthma group. The eosinophil level was not found to be statistically associated with the CD14 gene promoter SNPs in either the atopic asthma or non-atopic asthma groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The findings of this case–control study among 324 American Indian children in the Northern Plains of the United States are largely in accord with previous evidence of increased biomarkers of inflammation and specific, immune sensitization. We demonstrated increased total IgE immunoglobulins among those with asthma (although not in a multivariate model including a measure of specific sensitization), as also reported in studies of European [ 12 , 23 – 25 ], Han Chinese [ 26 ], African Americans and various Hispanic populations [ 11 , 27 ]. Other studies have been unable to find an association between total IgE and asthma [ 28 ] or found this association holds only among those with atopic sensitization to specific antigens [ 29 ].…”
Section: Discussionsupporting
confidence: 86%
“…The findings of this case–control study among 324 American Indian children in the Northern Plains of the United States are largely in accord with previous evidence of increased biomarkers of inflammation and specific, immune sensitization. We demonstrated increased total IgE immunoglobulins among those with asthma (although not in a multivariate model including a measure of specific sensitization), as also reported in studies of European [ 12 , 23 – 25 ], Han Chinese [ 26 ], African Americans and various Hispanic populations [ 11 , 27 ]. Other studies have been unable to find an association between total IgE and asthma [ 28 ] or found this association holds only among those with atopic sensitization to specific antigens [ 29 ].…”
Section: Discussionsupporting
confidence: 86%
“…There were 210 DEGs in ciliated cells in the WT-HDM vs. WT-Sal comparison (Figures 3A and 4C,D and Tables S5 and S6). Some DEGs from this comparison, such as Fos [37], Jun [38], Hes1 [39], Cd14 [40], and C3 [31], have been associated with asthma pathogenesis. Subsequently, we identified 96 significantly enriched pathways in these DEGs (Table S8).…”
Section: Exposure To Hdm Led To Cell Type-specific Changes In the Epc...mentioning
confidence: 97%
“… 22 Another study in a Chinese population has shown that the frequency of CD14 rs2569191 A-allele in allergic asthma is significantly lower than that in non-allergic asthma. 39 Moreover, we believe that although AR and asthma share many similarities, the inhibitory effects of genetic variations in TLR pathway on AR, asthma or other allergic diseases may differ to some extent, as Micheal et al 28 confirmed that in Pakistani adults, the CD14 rs2569191 is significantly associated with atopic asthma, but not AR.…”
Section: Discussionmentioning
confidence: 84%